Poly-3-hydroxybutyrate production from acetate by recombinant Pseudomonas stutzeri with blocked L-leucine catabolism and enhanced growth in acetate - Zhu, Jieni; Liu, Wei; Wang, Mengjiao; Di, Haiyan; Lü, Chuanjuan; Xu, Ping; Gao, Chao; Ma, Cuiqing (Frontiers in Bioengineering and Biotechnology, 2023)
Acetate is a low-cost feedstock for the production of different bio-chemicals. Electrochemical reduction of CO2 into acetate and subsequent acetate fermentation is a promising method for transforming CO2 into value-added chemicals. However, the significant inhibitory effect of acetate on microbial growth remains a barrier for acetate-based biorefinery. In this study, the deletion of genes involved in L-leucine degradation was found to be beneficial for the growth of Pseudomonas stutzeri A1501 in acetate. P. stutzeri (Δpst_3217), in which the hydroxymethylglutaryl-CoA lyase catalyzing β-hydroxy-β-methylglutaryl-CoA into acetyl-CoA and acetoacetate was deleted, grew faster than other mutants and exhibited increased tolerance to acetate. Then, the genes phbCAB from Ralstonia eutropha H16 for poly-3-hydroxybutyrate (PHB) biosynthesis were overexpressed in P. stutzeri (∆pst_3217) and the recombinant strain P. stutzeri (∆pst_3217-phbCAB) can accumulate 0.11 g L −1 PHB from commercial acetate. Importantly, P. stutzeri (∆pst_3217-phbCAB) can also use CO2-derived acetate to produce PHB and the accumulated PHB accounted for 5.42% (w/w) of dried cell weight of P. stutzeri (∆pst_3217-phbCAB).